Validation of Bakas Caregiving Outcome Scale for brazilian portuguese - Tatiana Ferreira da Costa; Cláudia Jeane Lopes Pimenta; Maria Miriam Lima da Nóbrega; Maria das Graças Melo Fernandes; Jordana de Almeida Nogueira; Kátia Neyla de Freitas Macedo Costa (Universidade de São Paulo, 2020)
Objective: to analyze the psychometric properties of the adapted version of Bakas Caregiving Outcome Scale for Brazilian Portuguese. Method: this is a cross-sectional methodological study conducted with 151 informal caregivers of people with cerebral vascular accident sequelae enrolled in Family Health Units. To assess reliability, Cronbach's alpha was used. Construct validity was verified through exploratory factor analysis, confirmatory factor analysis and correlation with measures of instruments that evaluate correlated constructs. Results: Cronbach's alpha for the total BCOS score was 0.89. Factor and exploratory analysis generated a one-factor structure, which was confirmed by confirmatory factor analysis. Construct validity was supported by the high positive correlations with Negative Affect (r = 0.51) and Negative Experience (r = 0.47) of the Well-being Scale and the Depression Anxiety and Stress Scale -21 (r = 0.53) and negative correlations with Positive Affect (r =-0.47) and Positive Experience (r = -0.17) of the Well-being scale. Conclusion: Bakas Caregiving Outcome Scale shows evidence of satisfactory reliability and validity in family caregivers of cerebral vascular accident survivors.